The Effect of Surface Waves on Power Conversion Efficiency of Underwater Solar Panels - Ninta, Jakrawut; Intaniwet, Akarin (Research on Modern science and Utilizing Technological Innovation Journal (RMUTI Journal), 2022)
This work reports the effect of surface waves on the power generation of solar panels. The experiments were carried out to determine the optimal wave characteristics for solar panels to generate maximum power when installed under water at the depth of 1 cm. Several electrical parameters were obtained under natural sunlight and ambient conditions for the comparison. The results were used to create a mathematical model which was used to predict the annual power generation of underwater solar panels. The key parameters employed in the prediction of the annual solar power generation included solar radiation, ambient and panel temperature. The results revealed that the solar panel installed underwater with surface wave height of 0.3 cm showed the highest power conversion efficiency of 24.06 %, compared to 12.78 % from the one installed on land. The annual power generation of an installed underwater solar panels with the surface wave height of 0.3 cm and capacity of 1 MW was estimated, by a mathematical model, to provide an yearly income of 9,804,636 THB, which was 227,059 THB higher than that from the on-ground installation system.